Implant Treatment with 12-Year Follow-Up in a Patient with Severe Chronic Periodontitis: A Case Report and Literature Review - Keisuke Seki; Yoshiyuki Hagiwara (Case Reports in Dentistry)
Tooth loss among adults is associated with progressive periodontitis. Implant prosthetic treatment has long been utilized in periodontal patients. Even when the implants are applied, ongoing management of periodontal disease and control of inflammation is necessary to maintain a healthy oral cavity. Lack of appropriate periodontal treatment can result in recurrence of periodontal disease during a maintenance period; loss of the supportive capacity of the periodontal tissues will increase the susceptibility of residual teeth to traumatic force. For this reason, it is worthwhile to improve oral function by applying implants as a fixed device. Here, we report that implant treatment in a patient with generalized severe chronic periodontitis helped maintain the periodontal and peri-implant tissue for a long term. We propose that initial periodontal treatment and ongoing supportive therapy can help maintain implants in patients with severe periodontitis. In addition, we reviewed case reports in the English literature so far.